Khurshid Dustmuhammad’s Interpretation of a Historical Figure in the Story "Qazo Bo`Lgan Namoz" - Odilbek qizi, Khajikurbanova Nilufar (European Journal of Life Safety and Stability (2660-9630), 2021)
In this thesisthe life of the image of MirkomilMirmominbaev in KhurshidDustmuhammad’s "Qazobo’lgannamoz" and the historical significance of his work for the development of the homeland are described. The character’s self-consciousness and desire to enlightenment are mentioned.